GIS-Based Aesthetic Appraisal of Short-Range Viewsheds of Coastal Dune and Forest Landscapes - Urbis, Arvydas; Povilanskas, Ramūnas; Jurkus, Egidijus; Taminskas, Julius; Urbis, Domantas (Forests, 2021)
This paper demonstrates the possibilities of a Geographical Information System (GIS) for investigating and explicating the spatial variation of the short-range viewshed aesthetic appeal in a World Heritage coastal dune and forest area. The study pursues the following objectives: (1) develop and trial a GIS-based algorithm for computing the Aesthetic Appeal Index for a Short-Range Viewshed (ǣ); (2) deliver an output map showing the spatial variation of the computed ǣ values in the target territory and distribution of the zones with high scenic quality and potential aesthetic ecosystem services (PAES); and (3) assess management alternatives in zones with high PAES and high conservation value. This study combines two key innovative aspects. First, it integrates an objective digital map of habitats with subjective scenic preferences of coastal forest and dune landscapes based on psychophysical and cognitive perceptions of scenic beauty. Second, it applies a GIS-based algorithm to translate subjective scenic preferences to an output map of ǣ. The study’s main conclusion is that the combined aesthetic appraisal of the immediate and foreground viewshed of coastal forests and dunes, by applying a specially created GIS algorithm, allows an assessment of the scenic quality of this landscape reliably in statistical terms.